Т.В. Калинский и его собрание рукописных копий исторических документов и книг - Репринцева, В.А.; Reprintseva, V. (Київ : Видавництво Національної бібліотеки України ім. В.І. Вернадського., 2013)
Стаття присвячена українському громадському діячеві кінця XVIII - початку XIX ст. Т. В. Калинському. Розкривається його внесок у збереження унікальної вітчизняної рукописної спадщини, яка проливає світло на українську минувшину. The article is devoted to the disclosure of some names that played a role in the history of Ukraine. Their contribution to the preservation of the documentary backward, personality assessment of certain events, mentioned in their manuscripts, was discribed. Т. V. Kalinskiy is a Ukrainian public man of the end of XVIII - beginning of the XIX century. A through study and comparison of his autographs with handwrittings of several manuscripts in the collection was made. As a result some of them could be identified as Kalinskiy's ones.
Т.V. Kalinskyi and his collections of scribal copies of historical documents and books
Вера Репринцева, библиотекарь ЦНБ Харьковского национального университета имени В. Н. Каразина.
Keywords: Калинський Т.В. і його зібрання книг і рукописів; копії рукописних документів; маргінальні записи; козацькі літописи; Літопис Грабянки; Kalinskiy Т.V. and his collection of books and manuscripts; role of his own collection in the preserving of the cultural heritage of the past; marginal notes; Hrabianka's chronicle